Konsep Akad dan Perjanjian Dalam Perspektif Hukum Islam Dan Hukum Perdata - Arif, Muhammad; Sari, Widya (Berasan: Journal of Islamic Civil Law, 2022)
This paper aims to examine the concept of contract and agreement in the perspective of Islamic and Civil law. This is a literature review (library research). The data analysis method used is content analysis. The findings of this study reveal that both the provisions of Islamic law and the Civil Law related to contracts and agreements do not clearly describe the specific things that make a difference from the provisions of Islamic law and the provisions contained in the Civil Law. Based on this, of course at a glance it can be understood that contracts and agreements based on the provisions of Islamic law and the Civil Law are no different, because each requires the existence of a legal subject, legal object and legal substance itself which in real terms must be disclosed in the contract and agreement.